Evaluation of clinical, anthropometric and radiological data in patients with delayed eruption of upper frontal teeth - Malashenko Н. Ю. (Actual Dentistry, 2024)
Introduction. Delayed eruption of teeth is an urgent orthodontic problem, but in most cases, it is detected incidentally during a routine dental examination. It is therefore extremely important that dentists diagnose this pathology as early as possible, as early intervention can help prevent a variety of complications. The treatment of delayed eruption requires multidisciplinary cooperation between paediatric dentists, orthodontists, surgeons and orthopaedists. Aim. To evaluate clinical, anthropometric, and radiological parameters in children aged 7 to 14 years who have delayed eruption of upper front teeth. Material and Methods. The study was conducted on Ukrainians aged 7 to 14 years who had delayed eruption of teeth. The patients were divided into 2 groups: Group I (49 (44.9%)) included children aged 7 to 9 years with early mixed occlusion; Group II (60 (55.1%)) was made of individuals aged 10 to 14 years who had the final stage of mixed occlusion. The control group consisted of 18 individuals who had their oral cavities health improved and had normal occlusion. After a thorough history taking and external examination, we conducted the following studies: clinical, anthropometric, radiological, and statistical. Results. At the age of 7 to 9, boys with delayed eruption of teeth (DET) outnumbered girls, whereas at the age of 10 to14, girls with delayed eruption significantly outnumbered boys. Delayed eruption of maxillary canines was found in 80% of children aged 10 to14 years. It was revealed that the main causes of delayed eruption in children aged 7-9 years were trauma to the previous deciduous teeth (65.3%) and early extraction of the previous deciduous tooth (73.5%). Among those aged 10 to 14 years, a trauma to the primary teeth was found in 16.7% and early extraction in 73.3% of paediatric patients. As the children with delayed eruption of upper frontal teeth grew older, we observed considerable changes in the size of the jaws with inadequate space for eruption. The children had a predominantly vestibular position of the teeth (44%). We found tooth inclination angles of more than 15° in 52.3% of the children in the study groups. Conclusion. Based on the analysis of the data obtained from the medical history, clinical, anthropometric and radiographic examinations, it can be assumed that with increasing age, the number of teeth with an unfavourable position increases, which prevents their successful eruption into the dental arch. The lack of space for eruption is particularly detrimental to canines.